SENAM LANSIA ERGONOMIS MEMPERBAIKI TEKANAN DARAH LANSIA DI BANJAR KEPUH PEGUYANGAN DENPASAR-BALI (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Grow old is a natural process that everyone will experience and the changes impact on health problems. One of these changes is the deterioration of the cardiovascular system which impact on blood pressure. Actively doing exercise such as elderly gymnastics has been proven to prevent this functional loss. Moreover, ergonomic elderly exercise was applied in Banjar Kepuh Peguyangan and aimed to improve the blood pressure. The application of ergonomic elderly exercise involved 25 elderly and pre-elderly people. Gymnastics activities were carried out for 4 weeks by 3 times per week. Pre data collection was carried out before the exercise, and post data after 4 weeks of exercise. Data included sample identity and blood pressure. Data were analyzed by Wilcoxon's difference test was performed at (α=0.05). After exercising regularly for 4 weeks, the systolic blood pressure decreasing to 5.7 percent and diastolic blood pressure to 0.1 percent. The Wilcoxon Difference Test found that there was a significant difference in systolic blood pressure (p0.05) before and after exercise for 4 weeks. It is recommended that elderly exercise activities be carried out regularly because gymnastics has a positive impact on health, fitness, and blood pressure.